Induction of Senescence in Lung Cancer Cells by Qidongning Formula via the Transcription Factor EGR1 - Di Zhou MD; Wen-Xiao Yang MD; Cheng-Yan Wang MD; Cheng-Xin Qian MM; Ling Xu PhD; Chang-Sheng Dong PhD; Jie Chen MM; Ya-Bin Gong PhD (Integrative Cancer Therapies)
Background: The purpose of this study was to investigate the role of the early growth response gene 1 (EGR1) in inducing senescence in lung cancer cells by Qidongning Formula (QDF). Methods: Cell-Counting-Kit-8 was used to study the effect of QDF on A549 and NCI-H1975 cells proliferation. Senescence-associated β-galactosidase (SA-β-GAL) staining was used to examine the effect of QDF on cellular senescence. RT-qPCR analyses and Western blot were used to monitor the expression of EGR1 and the senescence-associated proteins p21 and p53. A rescue assay using an EGR1-overexpressing vector to explore whether EGR1 is a key target gene of QDF-induced lung cancer senescence. Bioinformatics analyses were used to identify the regulatory network involved in the process of QDF-induced senescence in lung cancer cells, downstream of EGR1 activation. Results: QDF could inhibit the proliferation of lung cancer cells in a concentration- and time-dependent manner. SA-β-GAL assay showed that QDF can induce lung cancer cells senescence, an increase in QDF concentration led to a significant increase in the number of cells that stained positive in the SA-β-GAL assay in the group exposed to a higher concentration of QDF. Western blot and RT-qPCR analyses indicated that the expression levels of the p53 and p21 proteins in A549 and H1975 cells increased significantly after QDF intervention. Additionally, EGR1-overexpressing can enhance QDF-induced senescence in lung cancer cells. Bioinformatics analyses revealed the EGR1 target genes implicated in QDF-induced senescence in A549 cells, including 21 senescence-related genes. Conclusion: The present study suggests QDF induces cellular senescence through activation of EGR1 in lung cancer cells and provides an insight for understanding the antitumor mechanisms of this Chinese traditional medicine.